Women’s attitudes towards genital aesthetic surgery and the effects of social media: A qualitative study in the context of Türk Muslim women - Barut, Sümeyye; Aydın, Tülay Aytekin; Akto, Gülşah (My University, 2024)
Aim: In the study, it was aimed to determine Türk Muslim women’s attitudes towards genital aesthetics procedures and investigate the effects of social media in this regard. Methods: In the collection of the data, the semi-structured interview technique, which is a qualitative method, was used. The study was completed with 11 women. The collected data were analyzed using the qualitative content analysis method. Results: As a result of the content analysis, 4 main themes and 10 subthemes were determined. The main themes were: (1) reasons for genital aesthetics procedures (childbirth-related problems, sexuality), (2) attitudes (the woman’s attitudes, society’s attitudes, beliefs), (3) obstacles and expectations (obstacles and expectations related to health service provision, scientific obstacles and expectations, privacy), and (4) social media (information, its effects on concerns). Conclusion: In this study, it was determined that women associated genital aesthetics procedures with sexuality and childbirth, they though these procedures should be performed in line with women’s needs, their beliefs would not prevent them from having these procedures in case they needed them, they had economic and systemic expectations regarding the subject in the provision of health services, and they mentioned the positive effects of social media in informing women and reducing concerns. It is recommended that health service providers make attempts to create appropriate environments and opportunities through which women can easily access information about genital aesthetics procedures, they inquire about women’s sexuality while providing care, and they have adequate information about genital aesthetics procedures.
Keywords: Genital; female; surgery; esthetics; Muslim; media social